Longitudinal consumption of fruits and vegetables and risk of asthma by 5 years of age. Issue 3 (13th March 2023) - Metsälä, Johanna; Vuorinen, Anna‐Leena; Takkinen, Hanna‐Mari; Peltonen, Essi J.; Ahonen, Suvi; Åkerlund, Mari; Tapanainen, Heli; Mattila, Markus; Toppari, Jorma; Ilonen, Jorma; Veijola, Riitta; Haahtela, Tari; et al.
Abstract: Background: Fruit and vegetable consumption has been linked to a decreased risk of asthma, but prospective evidence on longitudinal consumption in childhood is scarce. We aimed to investigate the association between fruit and vegetable consumption in childhood and the risk of asthma by the age of 5 years, and to explore the role of processing of fruits and vegetables in the Finnish Type 1 Diabetes Prediction and Prevention Allergy Study. Methods: Child's food consumption was assessed by 3‐day food records completed at the age of 3 and 6 months, and 1, 2, 3, 4, and 5 years, and asthma and allergies by a validated modified version of the ISAAC questionnaire at the age of 5 years. Consumption of processed and unprocessed fruits and vegetables was calculated. Joint models with a current value association structure for longitudinal and time‐to‐event data were used for statistical analyses. Results: Of the 3053 children, 184 (6%) developed asthma by the age of 5 years. The risk of asthma was not associated with the consumption of all fruits and vegetables together (HR 1.00, 95%CI 0.99–1.01 per consumption of 1 g/MJ, adjusted for energy and other covariates), or with most subgroups. Weak inverse associations were seen between all leafy vegetables and asthma (HR = 0.87, 0.77–0.99), and unprocessed vegetables and nonatopic asthma (HR = 0.90, 95% CI 0.81–0.98). Conclusion: Total consumption of fruits and vegetables in childhood was not associated with the development of asthma by the age of 5 years. Weak inverse associations found for vegetables need to be confirmed or rejected in future studies.